Double dispersion effect on nonlinear convective flow over an inclined plate in a micropolar fluid saturated non-Darcy porous medium - D. Srinivasacharya; Ch. RamReddy; P. Naveen (Engineering Science and Technology, an International Journal, 2018)
This article explores the influence of double dispersion on micropolar fluid flow past an inclined plate in a homogeneous and isotropic non-Darcy porous medium. Additionally, the effect of nonlinear Boussinesq approximation (i.e., also known as nonlinear convection) with the convective thermal condition is considered to address the heat and mass transfer phenomena in some thermal systems which are operated at moderate to very high temperatures. The governing partial differential equations are transformed into a system of ordinary differential equations using a local non-similarity method, and the resulting boundary value problem is solved using a novel successive linearization method (SLM). The accuracy of the SLM has been established by comparing the results with the shooting technique. This numerical study discusses the influence of pertinent parameters on the fluid flow characteristics through graphs and the salient features are discussed in detail. Heat and mass transfer varies extensively with the increase of nonlinear convection parameters, which depends on aiding and opposing flow situations. In the both aiding and opposing flows, thermal dispersion favors the heat transfer, whereas the solutal dispersion parameter benefits the mass transfer. This kind of investigation is useful in the mechanism of combustion, aerosol technology, high-temperature polymeric mixtures, solar collectors which are operated at moderate to very high temperatures. Keywords: Nonlinear convection, Convective boundary condition, Double dispersion, Micropolar fluid, Successive linearization method